Optimizing Human Resource Management in Improving the Quality of Academic and Non-Academic Services in Private Universities (Case Study at Universitas Pembangunan Panca Budi) - Rahmat Hidayat; Efrizal Adil lubis (Yayasan Multidimensi Kreatif, 2025)
Universities as educational service providers are required to provide the best service to create satisfaction for stakeholders, especially students. Universitas Pembangunan Panca Budi (UNPAB) as one of the leading private universities in North Sumatra is not spared from this challenge. This article discusses problems related to internal services and policies that have the potential to harm students, which if not addressed will have an impact on the reputation and sustainability of the institution. Using the perspective of Human Resource Management (HRM), this article offers a strategic solution that focuses on improving the competence and commitment of education staff (Tendik) and lecturers. The solutions offered include strengthening service excellence-based soft skills training, implementing a transparent reward and sanction system, and evaluating policies based on student participation. The implementation of the right MSDM strategy is expected to be able to transform the campus bureaucracy to be more responsive and in favor of student needs.